When you have a polynomial with no independent term you can start by factorizing the polynomial, as follows:
![h(x)=2x^4-x^3-18x^2+9x](https://img.qammunity.org/2023/formulas/mathematics/college/g0tc5wnuycw81dyo9w01tw2v663222fkys.png)
The common factor is x, then:
![h(x)=x(2x^3-x^2-18x+9)](https://img.qammunity.org/2023/formulas/mathematics/college/1fed6ew8kn2j2uluzpqppyn7mbbb769pgn.png)
Now you have a third-degree polynomial inside the ( ), let's called it j(x):
![j(x)=2x^3-x^2-18x+9](https://img.qammunity.org/2023/formulas/mathematics/college/2xwqud765rha1evx56wr40c8opah53yb2f.png)
You need to factorize this polynomial, then find all the numbers that divide the independent term 9.
These numbers are:
![1,-1,3,-3](https://img.qammunity.org/2023/formulas/mathematics/college/t2a0p3ep5qpubewzfhp9vqd3h81d3t1mcr.png)
Let's probe if any of these numbers makes j(x)=0:
![\begin{gathered} j(1)=2(1)^3-(1)^2-18(1)+9 \\ j(1)=2-1-18+9_{} \\ j(1)=-8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/p53f184khiono159utmovryuje7q53uauh.png)
Then 1 is not a root, let's try -1:
![\begin{gathered} j(-1)=2(-1)^3-(-1)^2-18(-1)+9 \\ j(-1)=-2-1+18+9 \\ j(-1)=24 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/bebzl16lkfxz058vbhu44m58plmihaj07l.png)
Then -1 is not a root, let's try 3:
![\begin{gathered} j(3)=2(3)^3-(3)^2-18(3)+9 \\ j(3)=2\cdot27-9-18\cdot3+9 \\ j(3)=54-9-54+9 \\ j(3)=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/rdnd456cp0y51xiybprgoz9ev8hzr8vwk5.png)
Then 3 is a root and you can apply synthetic division to find the others:
The new polynomial is:
![2x^2+5x-3](https://img.qammunity.org/2023/formulas/mathematics/college/n75lmmmerpjaxn4ff3fz978n7x21js8aph.png)
Now you can factorize it as follows:
![2x^2+5x-3=(2x-1)(x+3)](https://img.qammunity.org/2023/formulas/mathematics/college/14rm74hohzbmgs79ajsyx3yh4cfls4w8i5.png)
And finally, your 4th-grade polynomial can be written as:
![h(x)=x(x-3)(2x-1)(x+3)](https://img.qammunity.org/2023/formulas/mathematics/college/7qlv50v3xnmen1ym36migmslvr6pdthfc1.png)
Thus, the zeros are at:
![\begin{gathered} x=0 \\ (x-3)=0\text{ then x=3} \\ (2x-1)=0\text{ then x=1/2} \\ (x+3)=0\text{ then x=-3} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/efdt9wjewqkuc6gy73no5zp1plun9ehgum.png)
The answer is 0, 3, 1/2 and -3